Numerical simulation study on the energy dissipation characteristics of energy-dissipating pile-anchor structures - Ren Wang; Tong Luo; Xuecheng Liu; Tao Zhou; Xuanming Ding; Bo Zhang (PLoS ONE, 2026)
This study investigates the energy dissipation mechanisms and damage evolution of energy-dissipating and ductile pile-anchor structures under seismic loading through numerical simulation. A three-dimensional finite element model was developed, incorporating the Concrete Damaged Plasticity model for simulating concrete behavior, a microscopic model for Fiber-Reinforced Concrete, specifically Engineered Cementitious Composite, and a static-dynamic boundary conversion method to enhance analysis accuracy. A series of parametric studies were conducted to analyze the effects of pile stiffness, pile-soil interface roughness, and the use of Engineered Cementitious Composite ductile members on the structural response. Key findings indicate that: (1) The Concrete Damaged Plasticity model combined with the 3D microscopic model effectively simulates the dynamic damage characteristics of concrete and Engineered Cementitious Composite. (2) Increasing pile stiffness reduces pile damage but can increase soil plastic deformation beyond an optimal point, highlighting the need for balanced stiffness and deformation capacity. (3) Increasing the pile-soil friction coefficient alters the failure mode and energy dissipation pattern of the pile due to changes in eccentric axial force and additional bending moment. (4) Engineered Cementitious Composite members significantly reduce structural damage and enhance energy dissipation capacity, particularly under strong seismic motions, by maintaining integrity and fully activating damping devices.